Penyuluhan Metode Akupresure Terhadap Nyeri Haid Pada Siswi MA Al-Junaidiyah Biru : Counseling on the Acupressure Method for Menstrual Pain At MA Al-Junaidiyah Biru students - Musni, musni; Ita Novianti; St. Malka; Sitti Fatimah; Kiki Reski Rahmadani; Mutmainnah Mutmainnah; A.Ulfa Fatmasanti; Asrianti Safitri Muchtar (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Period teenager is period of the reproductive system already experience maturity for reproduce so that on period teenager also already experience menstruation. wrong a common syndrome happen in the menstrual process is painful period. this syndrome the symptoms different different each individual wrong only one is dizziness,nausea,abdominal pain, constipation until faint so that could disturbing activity. For resolve problem the can do  treatment in a manner pharmacology with consume drugs and can also use remote method  more safe from on consuming medicine is method therapy acupressure. Purpose devotion this give education about acupressure therapy as alternative method for treat painful period. live use method belended learning (lectures, QandA, and practicum) was carried out for 33 female students to make it easy understand what is conveyed and capable apply it in life everyday.Results activity counseling this is happen enhancement significant to knowledge female student about acupressure method for treat dysmenorrhea